Drying behaviour of second-growth Nothofagus alpina - Rubén A. Ananias; Gonzalo Hernandez; Emilio Vergara (Maderas: Ciencia y Tecnología, 2014)
Wood drying quality and transversal permeability of Chilean second-growth Nothofagus alpina (raulí) were evaluated. Two charges of  raulí sawnwood were dried in a experimental kiln. One of the charges was prepared with sawnwood from Pinto the second one was prepared with sawnwood from Collipulli. The transverse permeability to air of the material after drying was determined. The results showed that the drying rate was 25% higher and drying time was about 18% shorter for Collipulli sawnwood (from green to 12%) due to the extent of heartwood.  The shrinkage, collapse and drying stress were less in the wood dried from Collipulli, while the transverse permeability was lower in the samples from Pinto.